Kinematics Simulation of the Cam Mechanism of the Zipper Machine Based on ADAMS. (October 2019) - Li, Canjun; Zeng, Wenhao; Xu, Dawei; Yang, Yongtai
Abstract: The metal zipper forming process is complicated in process, and the coordinated movement of each component is closely related. In order to more thoroughly understand the zipper chain forming process, and clearly show the coordinated action process of the metal zipper parts, the kinematics simulation of the metal zipper punching and punching mechanism. The results of the motion simulation can also check whether the design of the mechanism is correct or not, and whether there is structural interference between the components. The virtual prototyping technology can fully reveal the motion state of each component of the machine. The simulation results show that the punching and punching mechanism performs the kinematic data of the end punching needle. By analyzing these data, the motion law of the end of the mechanism can be analyzed to pave the way for further optimization of the mechanism.